Cohesion Deficiencies in Eastern and Central Europe – Inequalities of Regional Research Area - Horváth, Gyula (Discussion Papers, 2012)
Regional diversity in the European Union increased sharply with the enlargement. The present EU regions are already characterized by substantial income, employment and pro¬ductivity disparities reflecting differing resource endowments and innovation performance. These features include physical and social infrastructure, the skills of the work force, an institutional framework and culture conducting to innovation and the efficiency of public institutions (especially managerial capacity) at the regional level. This paper introduces the Central and Eastern European situation of regional disparities. Besides the analyses of the transformation processes in the regions it draws a picture of urban systems influencing improvement of the regions and localities in six medium-sized Central and Eastern European countries. The second aim of this paper is to identify regional differences in the R&D structure of EU member states in Eastern and Central Europe. The basic hypothesis is that exaggerated intellectual polarisation hampers the strengthening of regional cohesion and that R&D must be given a priority role in economic development strategies. This notion has not yet been realised in the operative programmes of National Development Plans. The strengthening of R&D featured prominently in the Lisbon criteria, but only a few words were devoted to the regional dissemination of intellectual potential, R&D capacity and knowledge-intensive fields of activity. Conditions suitable for innovative development are simply not yet available in most European regions.